Code Mixing Used In Cinta Laura Youtube Channel’s “Bicara Cinta” - Ni Kadek Aprilia Dwi Astari; I Made Yogi Marantika (Wanastra: Jurnal Bahasa dan Sastra, 2023)
This study purpose is to found: 1) code mixing types used in Cinta Laura video podcast “Bicara Cinta” on YouTube channel and 2) the factors why the speakers used code mixing in video podcast “Bicara Cinta” on YouTube channel. This study applied the theory of Hoffman (1991). Code Mixing is a study of sociolinguistics. Sociolinguistics can be defined as the study of language that related to society. Sociolinguistics is concerned with how language use interacts with or is influenced by social factors such as gender, ethnicity, age, and social class. Sociolinguists are interested in how we change the way we speak in different social contexts and how we use specific features of language to convey aspects of social meaning and identity. The data were taken from a video podcast “Bicara Cinta” from Puella Id YouTube channel owned by Cinta Laura. This study used a descriptive qualitative method, in Observations method, watching the video podcast, listening the conversation the video podcast, and note taking technique was applied in order to collecting data. The study result is showing the prominent type of code-mixing found in this study is Intra-sentential code-mixing, while the least type of code-mixing found in this study is Intra-lexical code-mixing. For occurrence from this data that found are 50 data, Type of code mixing Intra-sentential code mixing are 35 (70%), Intra-lexical code mixing is 6 (12%), and Involving a change of pronunciation are 9 (18%).  To get data results from involving a change of pronunciation, people need to understand the correct pronunciation, for example “of course” can be mispronounced to be “of cos” in this study.